DEVELOPING TASK RELATED TEXT: FROM COMPREHENSION TO COMMUNICATIVE COMPETENCE - ACHMAD FAIZIN; DANIA RAHMANITA (Fakultas Sastra Universitas Gresik, 2016)
This paper is aimed to discuss the importance of selecting the appropriate texts and tasks for reading comprehension. The different text offers opportunities for different kinds of exploitation and tasks related to the text. The more exploitable the text is, the more tasks can be varied. The activities include ones for pre-reading, whilst reading and post-reading forms of activities. Most of the tasks use multiple choice forms of questioning since the language and the content of the text is fairly challenging for SLTP students. The tasks themselves take the form of comprehension practices and a communicative task at the end.